Graphene and Carbon Nanotube‐based Electrochemical Sensing Platforms for Dopamine. Issue 22 (27th September 2021) - Islam, Santa; Shaheen Shah, Syed; Naher, Shamsun; Ali Ehsan, Muhammad; Aziz, Md. Abdul; Ahammad, A. J. Saleh
Abstract: Dopamine (DA) is an important neurotransmitter, which is created and released from the central nervous system. It plays a crucial role in human activities, like cognition, emotions, and response to anything. Maladjustment of DA in human blood serum results in different neural diseases, like Parkinson's and Schizophrenia. Consequently, researchers have started working on DA detection in blood serum, which is undoubtedly a hot research area. Electrochemical sensing techniques are more promising to detect DA in real samples. However, utilizing conventional electrodes for selective determination of DA encounters numerous problems due to the coexistence of other materials, such as uric acid and ascorbic acid, which have an oxidation potential close to DA. To overcome such problems, researchers have put their focus on the modification of bare electrodes. The aim of this review is to present recent advances in modifications of most used bare electrodes with carbonaceous materials, especially graphene, its derivatives, and carbon nanotubes, for electrochemical detection of DA. A brief discussion about the mechanistic phenomena at the electrode interface has also been included in this review. Abstract : Dopamine (DA) is a critical neurotransmitter, created and released from the central nervous system. The aim of this review is to present recent advances in modifications of most used bare electrodes with carbonaceous materials, especially graphene, its derivatives, and carbon nanotubes, for electrochemical detection of DA.